ANALISIS TINGKAT BRAND LOYALTY PADA PRODUK PEMBERSIH WAJAH MEREK â€œPONDSâ€ - Linanita Oktarina Efendi; P Didit Krisnadewara (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2013)
Paradigm or new marketing concepts, more emphasis on long-term relationships that are performed continuously between consumers and producers. In other words, the concept of a new marketing emphasis on consumer loyalty to the company or brand. This study was conducted to determine the level of brand loyalty in the consumer products brand Pondâ€™s facial cleanser and examine diferences in the assessment of consumer products brand Pondâ€™s facial cleanser in terms of diferences in consumer characteristics. Data were analyzed from 137 consumers of the brand Pondâ€™s facial cleanser. Te results of the study provide information that, 64.2 % of consumers achieve a level of committed buyer superbly, while the lowest rate (switcher) contained 16.8 % of respondents who like moving brand facial cleanser products. Oneway ANOVA analysis results are known there is a diference in the dimensions of consumer ratings committed buyer based on diferences in age, and the satisfed buyer dimensions, the liking of the brand, and committed buyer based on diferent jobs.Keywords:Â switcher, habitual buyers, satisfed buyer, the liking of the brand, committed buyer customer loyalty.